Peran kader posyandu dalam memberdayakan masyarakat Bintan - Fino Susanto; Mora Claramita; Sri Handayani (Berita Kedokteran Masyarakat (BKM), 2017)
Role of posyandu cadres in empowering the community of BintanPurposeThis study aimed to determine the role of posyandu cadres in empowering the community in Kawal village, Gunung Kijang district, Bintan regency.MethodsThis study used a qualitative method with a case study design and purposive sampling technique, with the cadres of posyandu. Data collection was done by in-depth interviews and focus group discussion (FGD), with triangulation of sources and methods.ResultsThe role of cadres are as a health motivator, with the extension officers of the health and medical services as well as cadres being able to identify the needs, barriers and help to coordinate in providing health services.ConclusionPosyandu cadres have high social spirit created by the combination of internal and external motivation, resources and potential as well as experience developing ability, with the social spirit capable of inspiring, activating, stimulating, mobilizing and motivating people.